Metapopulation patterns of additive and nonadditive genetic variance in the sea bass (Dicentrarchus labrax). Issue 8 (21st March 2017) - Guinand, Bruno; Vandeputte, Marc; Dupont‐Nivet, Mathilde; Vergnet, Alain; Haffray, Pierrick; Chavanne, Hervé; Chatain, Béatrice
Abstract: Describing and explaining the geographic within‐species variation in phenotypes ("phenogeography") in the sea over a species distribution range is central to our understanding of a variety of eco‐evolutionary topics. However, phenogeographic studies that have a large potential to investigate adaptive variation are overcome by phylogeographic studies, still mainly focusing on neutral markers. How genotypic and phenotypic data could covary over large geographic scales remains poorly understood in marine species. We crossed 75 noninbred sires (five origins) and 26 dams (two origins; each side of a hybrid zone) in a factorial diallel cross in order to investigate geographic variation for early survival and sex ratio in the metapopulation of the European sea bass ( Dicentrarchus labrax ), a highly prized marine fish species. Full‐sib families ( N = 1, 950) were produced and reared in a common environment. Parentage assignment of 7, 200 individuals was performed with seven microsatellite markers. Generalized linear models showed significant additive effects for both traits and pleiotropy between traits. A significant nonadditive genetic effect was detected. Different expression of traits and distinct relative performances were found for reciprocal crosses involving populations located on each side of the main hybrid zone located at the Almeria‐Oran front, illustrating asymmetric reproductive isolation. The poor fitness performance observed for the Western Mediterranean population of sea bass is discussed as it represents the main source of seed hatchery production, but also because it potentially illustrates nonadaptive introgression and maladaptation. Abstract : Noninbred sires and dams of the sea bass ( Dicentrarchus labrax ) were crossed to investigate geographic variation for early survival and sex ratio in recognized population units of this species. Significant additive and nonadditive effects were detected for both traits. Results have implications for a better understanding of reproductive isolation among wild populations and also potentially illustrate nonadaptive introgression and maladaptation.